Tangis Bundo Kanduang: Sub-Altern Perempuan Minang dalam Tradisi Bajapuik di Pariaman - Juliandi, Budi; Reza Fadil, Muhammad (STAINI Press, 2023)
The Bajapuik tradition describes the ongoing process of patriarchal ideological hegemony in social relations, in which the interests of the male community as a superior class are hidden, and the social rights of women as members of society are suppressed. This is a portrait of the process of gender discrimination. In the case of the bajapuik tradition, no matter how high the achievements of women and no matter The bajapuik tradition describes the ongoing process of patriarchal ideological hegemony in social relations, in which hidden the interests of the male community as a superior class, there is a suppression of women's social rights as members of society. This is a portrait of the occurrence of the process of gender discrimination. In the case of bajapuik tradition, no matter how high the achievements of women and how high the intellectual qualities of women still cannot raise their social status on par with men. This article wants to know how the struggle between customary tradition and Islamic law occurred in the Bajapuik tradition in Pariangan. Through qualitative research, it was concluded that the debate between adat and sharia in Minangkabau, adat always emerged as the main winner, especially in terms of bajapuik marriage. Sharia principles that emphasize women's rights are often left behind by customary domination. In the name of respect for custom, the bajapuik tradition increasingly provides greater benefits to the male side.how high the intellectual quality of women still cannot elevate their social status to equal with men